P044 Transcriptome analysis identifies dysregulated pathways and targets for therapy in patients undergoing surgical resection for Crohn's disease. (27th May 2021) - Akiror, S; Acharjee, A; Jeffery, L; Shivaji, U N; Zardo, D; Gkoutos, G; Ghosh, S; Iacucci, M
Abstract: Background: In Crohn's disease, intestinal strictures develop in 40% of patients often requiring repeated surgeries. Current treatments have limited efficacy. Therefore, better understanding of dysregulated molecular pathways is needed to identify targets for therapy. The aim of this study was to identify novel pathways involved in stricture pathogenesis. Methods: Patients undergoing resection for CD-related strictures were recruited (IRAS ID-248494). RNA was extracted from proximal, strictured and distal segments of resected ileal/ileo.cecal segments. cDNA libraries were prepared for 9 patients using QIAseq UPX 3' Transcriptome reagents and sequenced. Normalised expressions were obtained through the CLC-Genomics Workbench (Qiagen). Differentially expressed genes (adj.P.Val<0.05) were determined using the Limma package and PCA and PLS-DA modelling performed. Pathway-related genes were enriched using EnrichR. Area under the curve (AUC) analysis was done by the Random Forest method and qPCR used for gene validation. Results: Strictured, proximal and distal tissues had unique transcriptomes; stricture segment clustered separately from proximal and distal segments, which were very similar by comparison. 64 genes were commonly up-regulated and 17 down-regulated in stricture compared to either control segments. Pathway enrichment on these 81 genes identified 30 targets. 3 of 5 down-regulated genes, associated with the epithelial barrier (KLF5, KRKT20, DSK) whilst most up-regulated genes related to extracellular matrix and tissue remodelling (COL1A1, CTSK, HYAL2, GREM-1, SERPINE1), inflammation (PECAM1, CCL2, EDNRB, LY96, CTSK), adipogenesis (IGF-1, NDN, HADHA) and cellular stress. Based on statistical significance and biological relevance LY96, AKAP11, SRM, GREM1, EHD2, SERPINE1, HDAC1 and FGF2 were further studied for association with stricture. A combined AUC score of 0.979 (95%CI 0.902–1) confirmed strong association and was supported by qPCR validation with additional patients. (AUC=0.81, (0.56–0.95)). Conclusion: Loss of epithelial integrity, increased inflammation, tissue remodelling and adiposity characterise the stricture and may be modulated by existing anti-fibrotic drugs not tested in Crohn's disease as well as new drug development.